Differences in the Treatment of Benign Prostatic Hyperplasia: Comparing the Primary Care Physician and the Urologist - Rensing, Adam J. (Urol Pract, 2017)
INTRODUCTION: Benign prostatic hyperplasia is a prevalent chronic condition with expenditures exceeding $1 billion each year. Little is known about management of patients by primary care physicians compared to urologists. We assessed changes in management after medication initiation in these two settings. METHODS: From the Chronic Condition Warehouse 5% sample of Medicare beneficiaries linked to Medicare Part D data, we defined a cohort of men, 66 to 90 years old, with initial prescriptions for alpha-blocker, 5-alpha reductase inhibitor (5-ARI), or both. We assessed the initial change in therapy for up to four years after medication initiation: add a medication, switch medication, stop medication, or have surgery/retention. We estimated the cumulative incidence functions from competing risks data, and tested equality across groups (primary care physician vs. urologist). RESULTS: 5714 men started medication with a primary care physician, 1970 with a urologist. The most common change in treatment after medication initiation across all groups was medication discontinuation (55% alpha blocker; 46% 5-ARI; 30% combination therapy cumulative incidence at 3 years). Patients who started with primary care physicians were more likely to discontinue BPH-related medications, than patients with urologists (HR 1.19; 95% CI 1.09 – 1.29). The majority of patients who stopped alpha blocker therapy did not have further BPH therapy. CONCLUSIONS: Men given combination therapy are most likely to have continued medication use. Surgical therapy and retention are relatively rare events. Patients who initiate care with urologists are more likely to continue medical therapy than patients with care initiated by primary care providers.